Does the Chest Tube Removal Time Influence the Outcomes of Primary Spontaneus Pneumothorax First Episode Management? - Mongirdas, Matas; Untanas, Audrius; Jagelavičius, Žymantas; Janilionis, Ričardas (Lietuvos chirurgija, 2019)
Background / objectives. The main treatment option for the first episode of primary spontaneous pneumothorax is chest tube drainage, however, whether delayed chest tube removal might influence the recurrence is unclear. Methods. A prospective study, which included 50 patients, with an initial episode of primary spontaneous pneumothorax was performed. Patients were randomized into two groups according to the chest tube removal time: 1-day and 5-days after the air-leak has stopped. All patients were followed-up for at least six months. Both groups were compared according to the recurrence rate and possible complications. Results. There were 39 (78%) men and the median age was 27 (23–35) years. Successful management with a chest tube was achieved in 43 (86%) patients, others were operated on because of the continuous air-leak or relapse of the pneumothorax after the chest tube was removed. Significant difference was not found comparing groups by age, gender, side, tobacco smoking, alpha-1-antitrypsin level, rate of prolonged air-leak, necessity of surgery, and the mean follow-up time. There was a significant difference between groups in hospitalization time: 1-day group – 6 (4–12), 5-days group – 8 (7–10) days, p = 0.017. Five (20%) patients from 1-day group and 3 (12%) from 5-days group had a recurrence, however the difference was not significant (p = 0.702). There were no significant differences comparing groups by the recurrence time or complications. Conclusions. The recurrence rate of primary spontaneous pneumothorax was higher if the chest tube was removed earlier, however not significantly. More data and longer follow-up are necessary to confirm these findings.